Fundamentals of speech recognition - Rabiner Lawrence; Juang Biing-Hwang (Delhi Pearson Education, 2003)
Provides a complete description of the basic knowledge and ideas that constitute a modern system for speech recognition by machine.
Keywords: Automatic speech recognition; Speech processing systems